Study of Thermal Decomposition of the Copolymer Based on Polyethylene Glycol Fumarate with Acrylic Acid - Meyram Burkeyev; Yerkeblan Tazhbayev; Abylaikhan Bolatbay; Yelena Minayeva; Santay Davrenbekov; Yermauyt Nassikhatuly; Anna Kovaleva; Kamshat Kutzhanova; Akerke Kazhmuratova (Journal of Chemistry)
Thermal decomposition of the copolymer based on polyethylene glycol fumarate with acrylic acid (p-EGF:AA) at four different heating rates in a nitrogen atmosphere has been investigated by the dynamic thermogravimetry (TGA) method. The TGA curves show that the decomposition process occurs in several stages. The experimental data processed by the Kissinger–Akahira–Sunose and Friedman isoconversion methods made it possible to calculate the activation energy of the main decomposition stage. According to the calculations results, one can see that the values found by these methods do not strongly depend on the conversion. The Achar–Brindley–Sharp method has been applied to determine the compensation parameters. Then, using the compensation effect, the invariant kinetic parameters of the decomposition processes have been found. An experimental curve has been plotted to find the reaction model in comparison with theoretical ones.